2000
DOI: 10.1046/j.1460-9568.2000.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization‐dependent survival of cultured mouse cerebellar granule neurons is strain‐restrained

Abstract: Cerebellar granule neurons (CGNs) isolated from the rat are often used as a model system for the analysis of activity-dependent survival of neurons. These cells do not survive in culture without addition of a depolarizing agent (KCl or glutamate) to the medium. However, it has been reported that mouse CGN behave differently. Here we found that the requirement for depolarization for the survival of the mouse CGN was strain-dependent, which may be important for future analyses using transgenic animals. CGNs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Consistently, Fujikawa et al (2000) reported that the KCldependency of cerebellar granule neurons is strain-dependent and that especially cerebellar granule neurons from C57Bl/6J mice require KCl for survival. Similar to the cell densitydependent survival, the effect of KCl was suggested to be mediated by autocrine neurotrophic substances released into the culture medium upon stimulation (Bessho et al, 1993;D'Mello et al, 1993).…”
Section: Seeding Density and Cultivation Of Hippocampal Cortical Andsupporting
confidence: 52%
“…Consistently, Fujikawa et al (2000) reported that the KCldependency of cerebellar granule neurons is strain-dependent and that especially cerebellar granule neurons from C57Bl/6J mice require KCl for survival. Similar to the cell densitydependent survival, the effect of KCl was suggested to be mediated by autocrine neurotrophic substances released into the culture medium upon stimulation (Bessho et al, 1993;D'Mello et al, 1993).…”
Section: Seeding Density and Cultivation Of Hippocampal Cortical Andsupporting
confidence: 52%
“…We utilized our culture system to address this issue by subjecting these cells to chronic depolarization using a medium containing 31.5 mM potassium. This approach was chosen as it represents a well‐established and documented protocol to manipulate granule cell development and neurochemical maturation (Baader and Schilling, 1996; Mellor et al, 1998; Fujikawa et al, 2000). In low‐density cultures, this had no apparent effect on NeuN immunoreactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Cultures of cerebellar granular cells were prepared as described by Fujikawa et al (2000), with minor modifications. Briefly, cerebella obtained from the wild-type or GluR⑀1-KO mice at 6 -7 d of age were treated with 0.2% trypsin for 15 min at 37°C.…”
Section: Production Of the Glur⑀3 And Glur⑀1/⑀3 Knock-out Micementioning
confidence: 99%